The provision of wage incentives: A structural estimation using contracts variation - Xavier D'Haultfœuille; Philippe Février (Quantitative Economics, 2020)
We address empirically the issues of the optimality of simple linear compensation contracts and the importance of asymmetries between firms and workers. For that purpose, we consider contracts between the French National Institute of Statistics and Economics (Insee) and the interviewers it hired to conduct its surveys in 2001, 2002, and 2003. To derive our results, we exploit an exogenous change in the contract structure in 2003, the piece rate increasing from 20.2 to 22.9 euros. We argue that such a change is crucial for a structural analysis. It allows us, in particular, to identify and recover nonparametrically some information on the cost function of the interviewers and on the distribution of their types. This information is used to select correctly our parametric restrictions. Our results indicate that the loss of using such simple contracts instead of the optimal ones is no more than 16%, which might explain why linear contracts are so popular. We also find moderate costs of asymmetric information in our data, the loss being around 22% of what Insee could achieve under complete information.
Keywords: C14; D82; D86; 330; Incentives; asymmetric information; optimal contracts; nonparametric identification